Evolutionary and ecological patterns in body size, shape, and ornamentation in the Jurassic bivalve Chlamys (Chlamys) textoria (Schlotheim, 1820) - S. Nürnberg; M. Aberhan; R. A. Krause (Fossil Record, 2012)
Changes in body size have been the subject of numerous palaeontological and neontological studies, but despite several general postulated "rules", the underlying processes controlling them are still incompletely understood, and their broad applicability is debated. Here we utilise morphological and ecological data from the Jurassic marine bivalve Chlamys textoria (Schlotheim, 1820) to analyse spatial and temporal trends in body size and ornamentation. We find: (1) fluctuations in body size during the Jurassic and no support for Cope's rule (the tendency to increase body size over geological time within an individual lineage); (2) a gradual increase in the average height to length ratio of the valves during the Jurassic. In the absence of any obvious adaptive advantage we suggest genetic drift as the causal mechanism; (3) a significantly larger mean body size in mid-palaeolatitudes than in the Jurassic tropics, providing evidence for the validity of Bergmann's rule (the assertion that body mass increases with latitude); and (4) a complex relationship between the number of plicae and the environment, which we explain as an improvement towards camouflaging the shell.doi:10.1002/mmng.201200002